E- LEARNING PLATFORM FOR REFUGEE CHILDREN IN RWANDA - Rukhsar Ejaz Sheikh Sheikh; Palvinderjit Kaur Harnek Singh; Mohammad Namazee Bin Mohd Nizam (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This research looks to provide a solution for solving poverty in education and bridging the gap in education in developing countries such as Rwanda, whereby there is a high refugee population. Rwanda is very welcoming to refugees and have refugees from over 50 countries. The researcher believes that by providing education to refugees, the society will benefit highly and reduce the illiteracy rate in that country, which is starting to slowly decline. Future children are embracing education and the same right should be given to refugee children who have had to migrate from their countries due to political instability and climate change.